History of Russia from the earliest times to the rise of commercial capitalism. New introd. by J.D. Clarkson. Transl. and ed. by J.D. Clarkson and M.R.M. Griffiths, including three maps, glossary and notes (University Prints and Reprints, 1966)
With bibliogr. and index.